Assessment of airborne fungi from animal establishments in and around Kolkata, West Bengal - Bhattacharyya, Sayan; Dighe, Prashil; -, Ruchi; Raj, Atul; Banik, Amit; Chattopadhyay, UK (Eastern Journal of Medical Sciences, 2022)
Background: Airborne transmission of pathogenic Fungi to humans from the environment, animals, or other humans are very common and cause various disease like Aspergillosis, aspergilloma (fungus ball), allergic sinusitis, and allergic bronchopulmonary disease, Flu-like illness, chronic lung disease etc. Materials and methods: The present study was conducted to analyze fungi present in around the environment of local meat market, fish market and farms. This was determined through air quality sampling using the ‘Settle plate technique’ using SDA agar plate and were analyzed at 37°C and 25°C after incubation using Lactophenol cotton blue mount. Results: The highest number of fungi were isolated from farms (37%) followed by chicken shop (24%) , Mutton shop(23%) and fish shops(16%). Aspergillus flavus(21%) was prominent in chicken shop while AspergIllus fumigatus(19%) was prominent in Mutton shop. Fusarium (19%) and Rhizopus spp.(18%) were prominent in farm air. Conclusion: The study is significant from One health point of view and stresses the importance of proper ventilation , sanitation and importance of sunlight in order to minimize load of fungi in air.